Interethnic Interaction in Medan: Challenges and Opportunities in a Multicultural Society - Al Zufri Al Zufri; Pujiati Pujiati; Nursukma Suri; Rahimah Rahimah (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
Medan stands as one of Indonesia’s most multicultural cities, exhibiting intricate social dynamics shaped by its deep-rooted ethnic diversity. This study aims to examine interethnic social interactions in Medan while identifying the challenges and opportunities for fostering social integration. The primary research questions explore the historical development of ethnicity in Medan, the factors influencing interethnic interactions, and the mechanisms through which challenges such as discrimination and social inequality can be mitigated. Employing a descriptive-analytical approach, this study investigates the historical formation of ethnicity in Medan and the evolving patterns of social interaction by analyzing historical records and social observations. The findings indicate that social interactions in Medan are influenced by colonial legacies, economic disparities, the role of religion, and education in shaping ethnic identity. Key challenges include social segregation, unequal access to resources, and identity politics, all of which impact social cohesion. Nonetheless, despite these challenges, Medan’s ethnic diversity remains a crucial asset for inclusive urban development, provided it is managed through a sustainable multicultural framework. This study contributes to a more comprehensive understanding of ethnic dynamics within Indonesia’s urban landscape.